Monocyte Plasminogen Activator Inhibitor 2 (PAI-2) Inhibits u-PA-mediated Fibrin Clot Lysis and Is Cross-linked to Fibrin - Ritchie, Helen; Robbie, Linda A.; Kinghorn, Seonag; Exley, Rachel; Booth, Nuala A. (Thrombosis and Haemostasis, 1999)
Plasminogen activator inhibitor 2 (PAI-2) is a major product of activated human monocytes. Here we show that monocytes inhibited u-PA- but not t-PA-mediated fibrinolysis, by secreting PAI-2 into an overlying fibrin clot. Extracts of arterial and venous human thrombi were found to contain active PAI-2. PAI-2 was cross-linked to fibrin in a reaction catalyzed by two major transglutaminases (TG), tissue TG and factor XIII. The activity of PAI-2 was not affected by such cross-linking. Cross-linking of PAI-2 to fibrin was inhibited by Tridegin, a specific inhibitor of TG, and also by EDTA and iodoacetamide. The use of competitive peptides mimicking the loop between helices C and D of PAI-2 identified Gln 83 and 86 as residues important in cross-linking. This study defines a mechanism by which PAI-2 is localized to fibrin, where it acts as an effective inhibitor of u-PA-mediated fibrinolysis.